HIV-1 RNA Levels and Antiretroviral Drug Resistance in Blood and Non-Blood Compartments from HIV-1–Infected Men and Women enrolled in AIDS Clinical Trials Group Study A5077 - Kantor, Rami (Public Library of Science, 2014)
BACKGROUND: Detectable HIV-1 in body compartments can lead to transmission and antiretroviral resistance. Although sex differences in viral shedding have been demonstrated, mechanisms and magnitude are unclear. We compared RNA levels in blood, genital-secretions and saliva; and drug resistance in plasma and genital-secretions of men and women starting/changing antiretroviral therapy (ART) in the AIDS Clinical Trials Group (ACTG) 5077 study. METHODS: Blood, saliva and genital-secretions (compartment fluids) were collected from HIV-infected adults (≥13 years) at 14 United-States sites, who were initiating or changing ART with plasma viral load (VL) ≥2,000 copies/mL. VL testing was performed on all compartment fluids and HIV resistance genotyping on plasma and genital-secretions. Spearman rank correlations were used to evaluate concordance and Fisher’s and McNemar’s exact tests to compare VL between sexes and among compartments. RESULTS: Samples were available for 143 subjects; 36% treated (23 men, 29 women) and 64% ‘untreated’ (40 men, 51 women). RNA detection was significantly more frequent in plasma (100%) than genital-secretions (57%) and saliva (64%) (P<0.001). A higher proportion of men had genital shedding versus women (78% versus 41%), and RNA detection was more frequent in saliva versus genital-secretions in women when adjusted for censoring at the limit of assay detection. Inter-compartment fluid VL concordance was low in both sexes. In 22 (13 men, 9 women) paired plasma-genital-secretion genotypes from treated subjects, most had detectable resistance in both plasma (77%) and genital-secretions (68%). Resistance discordance was observed between compartments in 14% of subjects. CONCLUSIONS: HIV shedding and drug resistance detection prior to initiation/change of ART in ACTG 5077 subjects differed among tissues and between sexes, making the gold standard blood-plasma compartment assessment not fully representative of HIV at other tissue sites. Mechanisms of potential sex-dependent tissue compartmentalization should be further characterized to aid in optimizing treatment and prevention of HIV transmission. TRIAL REGISTRATION: ClinicalTrials.gov NCT00007488